2017
DOI: 10.1093/cercor/bhx051
|View full text |Cite
|
Sign up to set email alerts
|

Mirroring the Social Aspects of Speech and Actions: The Role of the Insula

Abstract: Action and speech may take different forms, being expressed, for example, gently or rudely. These aspects of social communication, named vitality forms, have been little studied in neuroscience. In the present functional magnetic resonance imaging study, we investigated the role of insula in processing action and speech vitality forms. In speech runs, participants were asked to listen or imaging themselves to pronounce action verbs gently or rudely. In action runs, they were asked to observe or imaging themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…More specifically, Di Cesare et al (2016) using the same stimuli employed in the present study showed that observation of “rude,” “neutral,” and “gentle” vitality forms relative to controls produced activation of the dorso-central insula. Authors also found that the same area is also involved in the expression of action vitality forms ( Di Cesare et al, 2015 , 2017 ). Pooling together, these findings strongly suggest the existence of a mirror mechanism for action vitality forms in the dorso-central insula.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…More specifically, Di Cesare et al (2016) using the same stimuli employed in the present study showed that observation of “rude,” “neutral,” and “gentle” vitality forms relative to controls produced activation of the dorso-central insula. Authors also found that the same area is also involved in the expression of action vitality forms ( Di Cesare et al, 2015 , 2017 ). Pooling together, these findings strongly suggest the existence of a mirror mechanism for action vitality forms in the dorso-central insula.…”
Section: Discussionmentioning
confidence: 93%
“…While this study focused on visual information, it is important to stress that vitality forms may be conveyed by both visual and auditory information. In a recent study Di Cesare et al (2017) demonstrated that the central insula is a key region involved in both acoustical and visual vitality form processing. Furthermore, vitality forms do not coincide with emotions, since a single emotion (e.g., anger), may be expressed through multiple vitality forms (e.g., it may “explode,” “ooze out,” or “sneak up”; Stern, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a series of fMRI studies has demonstrated that this insular sector is involved in vitality form processing (Di Cesare et al, 2013 , 2015 , 2016a , b ). Additionally, Di Cesare et al ( 2017a ) have recently demonstrated that the dorso-central insula is activated not only when participants observed or imagined performing action vitality forms but also when they listened to or imagined pronouncing action verbs with gentle and rude vitality forms. These findings clearly indicate that the insular cortex has a role in the processing of multimodal vitality forms, suggesting the existence of a mirror mechanism specific for vitality forms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after having defined a suitable gesture language, as close as possible to established social standards, robot companions and human partners should be trained to use it in order to optimize symbiotic collaboration while minimizing mis-understanding. In other words, social robotics requires to define a social standard for well-educated human-robot symbiotic interaction, also taking into account what has been described as “vitality forms” of social communication (Di Cesare et al, 2018 ).…”
Section: Motor Intentions Machinery and Body Languagementioning
confidence: 99%